Activation inhibitors of nuclear factor kappa B protect neurons against the NMDA-induced damage in the rat retina - Kenji Sakamoto; Tatsuya Okuwaki; Hiroko Ushikubo; Asami Mori; Tsutomu Nakahara; Kunio Ishii (Elsevier, 2017)
We reported that high-mobility group Box-1 (HMGB1) was involved in excitoneurotoxicity in the retina. HMGB1 is known to activate nuclear factor kappa B (NF-ÎºB). However, the role of NF-ÎºB in excitotoxicity is still controversial. Here, we demonstrated that NF-ÎºB activation induced by NMDA led to the retinal neurotoxicity. Male SpragueâDawley rats were used, and NMDA (200Â nmol/eye) and bovine HMGB1 (15Â Î¼g/eye) were intravitreally injected. Triptolide (500Â pmol/eye), BAY 11-7082 (500Â pmol/eye), and IMD-0354 (7.5Â nmol/eye), NF-ÎºB inhibitors, were co-injected with NMDA or HMGB1. Retinal sections were obtained seven days after intravitreal injection. Cell loss in the ganglion cell layer was observed in the HMGB1- and the NMDA-treated retina. All of the NF-ÎºB inhibitors used in this study reduced the damage. BAY 11-7082 reduced the expression of phosphorylated NF-ÎºB 12Â h after NMDA injection, upregulation of GFAP immunoreactivity induced by NMDA 12 and 48Â h after NMDA injection, and the number of TUNEL-positive cells 48Â h after NMDA injection. The results suggest that NF-ÎºB activation is one of the mechanisms of the retinal neuronal death that occurs 48Â h after NMDA injection or later. Prevention of NF-kB activation is a candidate for the treatment of retinal neurodegeneration associated with excitotoxicity. Keywords: N-methyl-d-aspartic acid, Nuclear factor kappa B, High-mobility group Box-1, Retina